Household Over-Indebtedness in Russia - World Bank (World Bank, Washington, DC, 2020)
In the last three years, household debt has risen by a third as disposable income declined. Declining interest rates, ease of access to credit for consumers and poorly regulated microfinance lending practices led to fast growth in consumer debt. Consumer lending in the banking and microfinance segments has been growing in double digits in 2017-2018, reaching a total of RUB 14,90 trillion (USD 230,8 million), or 14 percent of the Russian GDP. At the same time, real disposable income has been declining: as of 2018, it is 13 percent below 2014 levels. Accelerated consumer lending has been monitored by the Central Bank of Russia to adjust the supply side of consumer finance, but no in-depth assessment has been made on how this has been affecting households. To provide a demand-side assessment, the World Bank Group in cooperation with the Russian Consumer Protection Service (Rospotrebnadzor) and the International Confederation of Consumer Societies (CONFOP) conducted an over-indebtedness study in 2018-2019. The objective of the study was to take a deeper look at the increasing levels of indebtedness of` individuals in Russia, provide a demand-side view on the issue and assess potential social and economic implications. The results of the study afford a unique perspective on the issue of consumer over-indebtedness in Russia and provide Russian financial-sector regulator and consumer-protection authorities with additional context for reviewing and adjusting their existing policies in the area of consumer protection, responsible lending and related areas. The study was conducted in a form of a survey covering over 4,000 individuals in 16 Russian regions.